Bridging the Gap Between Biofuels and Biodiversity Through Monetizing Environmental Services of Miscanthus Cultivation. Issue 10 (5th October 2020) - Von Cossel, Moritz; Winkler, Bastian; Mangold, Anja; Lask, Jan; Wagner, Moritz; Lewandowski, Iris; Elbersen, Berien; van Eupen, Michiel; Mantel, Stephan; Kiesel, Andreas
Abstract: Carbon neutrality in the transport sector is a key challenge for the growing bioeconomy as the share of biofuels has stagnated over the past decade. This can be attributed to basic economics and a lack of a robust market for these technologies. Consequently, more sustainable biomass supply concepts are required that reduce negative impacts on the environment and at the same time promote environmental services for sustainable agricultural cropping systems including erosion prevention, soil fertility improvement, greenhouse gas mitigation, and carbon sequestration. One promising concept is the cultivation of perennial biomass crops such as Miscanthus ( Miscanthus Andersson) as biofuel feedstock. In this study, the multiple environmental services provided by Miscanthus are first explored and subsequently monetized. Then the integration of Miscanthus cultivation for biomass production into European agricultural systems is assessed. One hectare of Miscanthus provides society with environmental services to a value of 1, 200 to 4, 183 € a −1 . These services are even more pronounced when cultivation takes place on marginal agricultural land. The integration of Miscanthus into existing agricultural practices aids both conservation and further optimization of socio‐economic welfare and landscape diversification. As these environmental services are more beneficial to the public than the Miscanthus farmers, subsidies are required to close the gap between biofuels and biodiversity that are calculated based on the provision of environmental services. Similar approaches to that developed in this study may be suitable for the implementation of other biomass cropping systems and therefore help foster the transition to a bioeconomy. Plain Language Summary: The transition to a nonfossil transport sector is one of the most difficult and at the same time crucial challenges of the growing bioeconomy. In order to provide enough sustainably sourced biomass for biofuel production, a vast range of requirements need to be fulfilled—first and foremost the use of marginal agricultural land under low‐input conditions. Only in this way is it possible to avoid land use conflicts with food crop cultivation and biodiversity conservation. However, the utilization of marginal agricultural land often entails economic disadvantages for farmers. These financial losses should be compensated for by the public sector, as long as the cropping system provides environmental services such as groundwater protection, climate regulation, moderation of extreme weather events, and habitat functions. Monetizing the environmental services using concrete examples is still uncharted scientific territory; existing promotion concepts must be assessed as underdeveloped. Key Points: Environmental services of the perennial lignocellulosic crop Miscanthus were monetized for marginal agricultural land in Germany Monetary value of Miscanthus cultivation accounts for 1, 200–4, 183 € a −1, three times higher than the value of the raw material for biofuel Monetizing environmental services bridges the gap between biofuels and biodiversity by promoting the use of second generation biofuels